2009
DOI: 10.1161/circinterventions.108.823443
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of the Nobori Biolimus A9-Eluting Coronary Stent With the Taxus Liberté Paclitaxel-Eluting Coronary Stent in Patients With Stenosis in Native Coronary Arteries

Abstract: for the NOBORI 1 Clinical InvestigatorsBackground-The newly developed Nobori coronary stent coated with a bioresorbable polymer, polylactic acid, and the antiproliferative agent Biolimus A9 has the potential to reduce restenosis by suppressing neointima formation. Methods and Results-We conducted a randomized (2:1), controlled trial comparing the Biolimus A9-eluting stent Nobori and the paclitaxel-eluting stent Taxus Liberté, in 243 patients (153 Nobori and 90 Taxus) at 29 centers in Europe, Asia, and Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 30 publications
4
89
0
4
Order By: Relevance
“…In the following paragraphs we will review and summarize the main findings from published randomized data of the Limus Eluted from a Durable vs Erodable Stent Coating (LEADERS) [28] , NOBORI [33,34] , Individualized Drug Eluting Stent System to Abrogate Restenosis (ISAR)-TEST-3 [35] and TEST-4 [36,37] with sirolimus (rapamycin), PAINT (percutaneous intervention with BIO-polymer based paclitaxel-eluting or sirolimus-eluting vs bare stents for de novo coronary lesions) [38] and EUCATAX [39] trials. Study and stent design of each trial is described in Table 1.…”
Section: Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the following paragraphs we will review and summarize the main findings from published randomized data of the Limus Eluted from a Durable vs Erodable Stent Coating (LEADERS) [28] , NOBORI [33,34] , Individualized Drug Eluting Stent System to Abrogate Restenosis (ISAR)-TEST-3 [35] and TEST-4 [36,37] with sirolimus (rapamycin), PAINT (percutaneous intervention with BIO-polymer based paclitaxel-eluting or sirolimus-eluting vs bare stents for de novo coronary lesions) [38] and EUCATAX [39] trials. Study and stent design of each trial is described in Table 1.…”
Section: Technologymentioning
confidence: 99%
“…In this trial [33,34] , 243 patients were randomized in a 2:1 ratio between Biolimus with BIO polymer stents (Nobori) and paclitaxel with durable polymer stents (Taxus).…”
Section: Nobori Trialmentioning
confidence: 99%
“…2,3 These techniques have effectively enhanced efficacy and safety of the DES as reported in the SPIRIT group of studies LEADERS, STEALTH, NOBORI 1 trial and Meri T-I studies. [4][5][6][7][8][9][10] Late lumen loss is considered as the surrogate of neo-intimal hyperplasia; the latter being an indicator of DES efficacy. 11 Whereas drug and its dose on the stent remains an important factor influencing neo-endothelial growth, the most important among mechanical factors is the strut thickness of the stent.…”
Section: Introductionmentioning
confidence: 99%
“…In-vivo studies conducted by Joner M. et al [91], demonstrated an improved reendothelialization in rabbits iliofemoral artery by the usage of DES. However, an excess of late loss (reduction in vessel diameter after stent implantation) [90], lack of reduction in stent thrombosis [92,93], and a high inflammatory reaction due to major particle debris (coating degradation),were some of the limitations of DES with biodegradable polymers. Consequently, the complex process of designing and developing a DES with biodegradable polymer coating remains a challenge.…”
Section: Evolution Of Drug Eluting Stentsmentioning
confidence: 99%
“…Figure 6.23 (a) and (b) show the modulus and hardness calculated by using the Oliver Pharr approach (depths above 1000 nm and peak loads above 25 mN). The modulus of NiTi alloys (79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98) increased with the addition of alloying elements as did the hardness (3-7.4 GPa) (see Table 6.4 and Figure 6.23). The significance of each peak observed in the aforementioned FTIR spectra is tabulated in Table 6.5.…”
Section: Determination Of Mechanical Properties Of Niti Alloys By Nanmentioning
confidence: 99%